2018
DOI: 10.1007/s10865-018-9918-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between daily pain and actigraphy sleep patterns in pediatric sickle cell disease

Abstract: Limited research is available on the relationship between objective sleep patterns and pain in children with SCD. Research in other chronic pain populations suggests that the effect of sleep disruption on pain may be stronger than the effect of pain on sleep that night. To examine the bi-directional relationship between objective sleep patterns and daily pain in a pediatric SCD sample. Participants were 30 African American children with SCD 8-18 years (13 ± 2.8 years; 66.7% female) with frequent pain. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
4
26
2
Order By: Relevance
“…38 They also may have disturbed sleep or sleep-disordered breathing. [39][40][41][42][43][44] Fatigue may be severe, with severe anemia, and correlates substantially not only with pain but with sleep quality, anxiety, depression, and stress 45 and neurocognitive function and decreased quality of life. 46 Poor interpersonal relationships at work have been reported to be a larger contributor to unemployment than physical health in individuals with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…38 They also may have disturbed sleep or sleep-disordered breathing. [39][40][41][42][43][44] Fatigue may be severe, with severe anemia, and correlates substantially not only with pain but with sleep quality, anxiety, depression, and stress 45 and neurocognitive function and decreased quality of life. 46 Poor interpersonal relationships at work have been reported to be a larger contributor to unemployment than physical health in individuals with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there were small-to-moderate associations between pain frequency/intensity and internalizing symptoms. Studies using youth self-report of internalizing symptoms reported small-to-moderate correlations with youth-reported pain frequency (Fisher et al, 2018;Karlson et al, 2017). Studies utilizing caregiver-reports of internalizing symptoms and pain frequency reported conflicting findings, with differences possibly related to the age range of study samples.…”
Section: Pain Frequency/intensity and Internalizing Symptomsmentioning
confidence: 99%
“…Five studies (17%) assessed internalizing symptoms, three of them utilizing a caregiver-report measure (Missouri Children's Behavior Checklist Internalizing scale) and two utilizing a youth-report measure (Revised Children's Anxiety and Depression Scale total score). Of the studies that looked at the relationship between pain and internalizing symptoms, the percentage of youth with clinically significant cut-off scores on internalizing measures ranged from 17 to 36% (Fisher et al, 2018;Karlson et al, 2017;Thompson, Gil, Burbach, Keith, & Kinney, 1993). Eight studies (28%) examined positive and negative affects, with all utilizing youth-report measures (Positive and Negative Affect Scale-Children was the most common) and two also using caregiver-report.…”
Section: Internalizing and Affective Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our mobile application study, >80% of the reports of aura were followed by pain. In another study (39), the sleep patterns of pediatric SCD subjects were monitored over 2 weeks using a wrist-mounted actigraphy device, and these were found to be associated with the occurrence of next-day pain recorded by daily pain diary. Taken together, these exciting recent developments point to the future possibility of embedding an ML-based model in a low-cost wearable system, consisting of a wristband paired with mobile phone, to assist clinicians in managing long-term therapy for SCD patients.…”
Section: Implications For Home-based Clinical Applicationmentioning
confidence: 99%